2014
DOI: 10.2147/ppa.s59371
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to improve adherence to pharmacotherapy in patients with schizophrenia

Abstract: PurposeIn patients with schizophrenia, nonadherence to prescribed medications increases the risk of patient relapse and hospitalization, key contributors to the costs associated with treatment. The objectives of this review were to evaluate the impact of nonadherence to pharmacotherapy in patients with schizophrenia as it relates to health care professionals, particularly social workers, and to identify effective team approaches to supporting patients based on studies assessing implementation of assertive comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…[1543] In this study, there was no difference between the two groups with respect to distance to the hospital or transportation charges. Thus, these factors may not distinguish between compliance and noncompliance.…”
Section: Discussionmentioning
confidence: 78%
“…[1543] In this study, there was no difference between the two groups with respect to distance to the hospital or transportation charges. Thus, these factors may not distinguish between compliance and noncompliance.…”
Section: Discussionmentioning
confidence: 78%
“…Detailed descriptions of the two trials have been published 20,21. These surveys were adapted from versions used in pilot studies conducted with patients and physicians sampled from online panels 18,19…”
Section: Methodsmentioning
confidence: 99%
“…In addition, adherence rates vary over time, even in the same individual [1]. Despite the view that medication adherence in schizophrenia is high after hospital discharge, the transition to home-based treatment may be complicated, especially for those individuals who lack family or social support [12]. Weiden et al [13], in a large observational study of patients with schizophrenia, found that almost half of the prescription gaps occurred in the first 50 days after starting a second-generation antipsychotic.…”
Section: Introductionmentioning
confidence: 99%